Developing Folktale-Based Student Worksheets to Improve Junior High School Students’ Collaboration Skills - Nafi’ah, Zahrotun; Utomo, Yudhi; Fatmawati, Denny (Teaching, Learning, and Development, 2026)
Collaboration skills are an important part of 21st century learning that needs to be developed in teaching and learning activities. However, the results of observations and interviews with teachers at one of junior high school student in Malang, Indonesia showed that science learning has not fully facilitated optimal student collaboration. One alternative solution that can be done is through the development of student worksheets based on local folklore that is contextual and encourages group cooperation. This study aims to develop student worksheets based on the folklore "Sumber Wendit", which is feasible and practical to use in science learning on food chain materials. The study used the Research and Development (R and D) method of the Borg and Gall model, which was modified and implemented until the product revision stage. The validation test was carried out by one expert validator, while the readability and practicality tests each involved 25 students and one science teacher. The results showed that the student worksheets were in the very feasible category in terms of content, language, presentation, and appearance. This student worksheets were also considered easy to understand by students and helped them work together in understanding the concept of the ecosystem meaningfully. Thus, this student worksheets is declared valid, practical, and has the potential to support strengthening collaboration in science learning.